2005
DOI: 10.5144/0256-4947.2005.375
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine monotherapy for severe aplastic anemia: a developing country experience

Abstract: BACKGROUNDImmunosuppression is the most effective treatment for aplastic anemia after hematopoietic stem cell transplantation. Although the combination of cyclosporine and antithymocyte globulin (ATG) is superior to either agent alone, cyclosporine monotherapy is an easily available, safe and cheap immunosuppressive therapy (IST) option. These advantages are particularly valuable in developing countries where ATG is frequently not available.PATIENTS AND METHODSIn the referral hematology center in Yemen, 20 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Cyclosporine is typically used in combination with ATG as IST, but due to nonavailability of ATG particularly horse ATG, financial constraints and lack of adequate blood components and other support facilities; it has been used as a single agent for treatment of acquired AA [63]. Most of the available evidence of CsA monotherapy outcomes come from small single center reports.…”
Section: Cyclosporine Monotherapymentioning
confidence: 99%
“…Cyclosporine is typically used in combination with ATG as IST, but due to nonavailability of ATG particularly horse ATG, financial constraints and lack of adequate blood components and other support facilities; it has been used as a single agent for treatment of acquired AA [63]. Most of the available evidence of CsA monotherapy outcomes come from small single center reports.…”
Section: Cyclosporine Monotherapymentioning
confidence: 99%
“…The epidemiological pattern in those regions probably do not apply to our country and possibly to other middle east countries although data from these countries have not been reported. The immunopathogenesis of our aplastic anaemic patients has been confirmed by their response to cyclosporin monotherapy (Al‐Ghazaly et al. , 2005).…”
Section: Discussionmentioning
confidence: 66%
“…Aplastic anaemia was the most common and was diagnosed in accordance with the well‐known criteria (Beutler et al. , 1995; Al‐Ghazaly et al. , 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Our results differ from those found in studies of CsA treatment for adults with SAA. Shetty et al recorded a 56.2% response rate to CsA in 20 adult patients with SAA after 3 months39, while Ghazaly et al found a 50% response in adults with SAA at 6 months [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…CsA is sometimes used alone as a monotherapy in countries with poor resources [ 15 , 16 ]. It is an effective immunosuppressant, inexpensive, accessible, can be administered to outpatients and is less toxic than combined treatment with ATG.…”
Section: Introductionmentioning
confidence: 99%